GYMNASTIC COMPLEX "U-XIN" - Джахангир Вагибович Шахмурадов (The Publishing House Medicine and Enlightenment, 2021)
The article presents a set of exercises based on one of the types of gymnastics developed by the ancient chinese physician Hua Tuo. Improvement of objective indicators of physical performance, well-being and academic performance was noted in 80 % of children.